VALIDITAS BUKU MODEL PERENCANAAN PEMBELAJARAN UNTUK SEKOLAH DASAR BERBASIS PENDEKATAN HUMANISTIK - Khairat, Annisaul; Yarhamna, Yarhamna; Fuaddin, Iskandar; Mardhiyah, Luqyana (JISPE Journal of Islamic Primary Education, 2022)
The aim of this research is to produce a book on a valid model of PAI learning planning and manners based on a humanistic approach. Research and development is the research methodology used (research and development). The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) was used in this development research. The validation sheet serves as a data collection instrument. The learning planning model based on Islamic and humanistic religious education for elementary schools was tested using a validation sheet. Aiken V's analytical methodology was used in the data analysis along with the qualitative and quantitative methodologies. The results showed that the validity of the learning planning model book for Islamic Religious Education and manners obtained an average of 0.79 with a valid category. Based on the description above, it can be concluded that the book on the learning planning model for Islamic religious education and character based on the humanistic approach developed can be declared valid